Accreditation Perspective in Improving School Performance at SMP Bisnis Aya Sophia Islamic School Tangerang - Asrofi, Imam; Arinindyah, Otisia; Nurhayati, Wakhida; Shofiyullah, Shofiyullah; Zawirrahmi, Zawirrahmi (International Journal of Social and Management Studies, 2025)
Educational accreditation is an important benchmark in assessing the quality and performance of educational institutions. This article aims to examine how the accreditation perspective contributes to improving the performance of Aya Sophia Islamic School Tangerang Business Junior High School. Using a descriptive qualitative approach and case study method, this study found that the application of strategy formulation, program planning, implementation, and monitoring based on accreditation indicators succeeded in improving the quality of graduates and the efficiency of school management. These results demonstrate the importance of accreditation as an instrument for fostering sustainable education quality.